KDF1, a Novel Tumor Suppressor in Clear Cell Renal Cell Carcinoma - Zheng, Jing-min; Gan, Mei-fu; Yu, Hong-yuan; Ye, Lu-xia; Yu, Qing-xin; Xia, Yu-hui; Zhou, Han-xi; Bao, Jia-qian; Guo, Yi-qing (Frontiers in Oncology, 2021)
KDF1 has been identified as a key regulator of epidermal proliferation and differentiation, but it is unknown whether KDF1 is involved in the pathogenesis of malignancy. No study has reported the expression and function of KDF1 in renal cancer. To explore the pathologic significance of KDF1 in clear cell renal cell carcinoma (ccRCC), the expression level of KDF1 protein in the tumor tissue of ccRCC patients was examined by immunohistochemistry and Western blot while the expression level of KDF1 mRNA was analyzed by using the data from TCGA database. In vitro cell experiments and allogeneic tumor transplantation tests were performed to determine the effects of altered KDF1 expression on the phenotype of ccRCC cells. Both the KDF1 mRNA and protein were found to be decreasingly expressed in the tumor tissue of ccRCC patients when compared with the adjacent non-tumor control tissue. The expression level of KDF1 in the tumor tissue was found to correlate negatively with the tumor grade. Patients with higher KDF1 in the tumor tissue were found to have longer overall survival and disease-specific survival time. KDF1 was shown to be an independent factor influencing the disease-specific survival of the ccRCC patients. Over-expression of KDF1 was found to inhibit the proliferation, migration and invasion of ccRCC cells, which could be reversed by decreasing the expression of KDF1 again. ccRCC cells with KDF1 over-expression were found to produce smaller transgrafted tumors. These results support the idea that KDF1 is involved in ccRCC and may function as a tumor suppressor.